Effect of Xingnao Kaiqiao (Brain Awakening through Opening Orifices) Acupuncture Method in Restoring Lower Limb Muscle Strength & Functions in Individuals with Acute Stroke - K.C., Pradeep; Satyal, Jaya; Shrestha, Rakesh; Pant, Basant; Xuemin, Shi (Annapurna Journal of Health Sciences, 2023)
Introduction: Stroke is a major cause of disability in adults worldwide. "Xingnao Kaiqiao" XNKQ or "awakening brain and opening orifices" acupuncture method is a therapeutic principle and acupuncture method for the basic pathogenesis of stroke. Yin and Du meridian acupoints are the main acupoints, and the quantitative norms of needling manipulation are emphasized, which are different from the traditional methods of Acupuncture. The main purpose of this study was to explore the effect of Xingnao Kaiqiao Acupuncture Method on recovery of lower limb muscle function in patients with acute stroke. Methods: It was a prospective, single blinded randomized controlled trial. Fifty patients with acute stroke and hemiplegia who met the diagnostic criteria were randomly divided into treatment group and control group with 25 cases in each group. The main acupoints used were Renzhong (DU 26), Neiguan (PC 6), Jiquan (HT 1), Chize (LU5), Weizhong (BL 40) and Sanyinjiao (SP 6). The differences between the two groups before and after treatment were compared, with statistical significance set at p-value less than < 0.05. Results: In our study, the mean age in intervention group was 55.68±14.23 years and in and control group it was 56.32±12.03 years. After intervention there was significant improvement in MTS, MMT, FMA-LE and MRS within and between groups (p=0.001). Difference in differences was evaluated and there was significant difference in intervention group after the end of session in each variable (MTS: p=0.001, MMT: p= 0.03, FMA-LE: p=0.021 and MRS: p=0.001). Conclusion: XNKQ Acupuncture method can significantly improve lower limb muscle strength and motor function in patients with acute stroke which is safe, low-cost, highly acceptable and effective treatment in Stroke